Phosphate Intoxication after Application of Enema - a Life-threatening Iatrogenic Complication - Marek, I.; Benz, Kerstin; Kusnik, Stefan; Morhart, P.; Botzenhardt, S.; Toni, I.; Rascher, Wolfgang (Klinische Pädiatrie, 2015)
Enemas are used in pediatric patients with constipation. Retention of phosphate containing enemas with prolonged resorption or reduced renal elimination of phosphate can result in life-threatening hyperphosphatemia with subsequent lethal hypocalcemia and acidosis.We report the case of a 6-month-old child who received phosphate-containing enema to treat acute aggravation of constipation. The used enema here was not licensed for this age group. Phosphate intoxication resulted (phosphate 19.87 mmol/l) and presented like a sepsis. Hyperphosphatemia was treated by hemodialysis. A non-diagnosed Hirschsprung disease had led to prolonged resorption of phosphate containing enema and to an ileus and toxic megacolon that had to be operated.Insufficient elimination of phosphate containing enema can result in lethal or life threatening hyperphosphatemia, hypocalcemia and metabolic acidosis. These can be treated efficaciously by hemodialysis. Because of the high risk of intoxication in using enemas containing phosphate in infants or in patients with gastrointestinal or renal comorbidities, physicians treating constipation should choose enemas without phosphate but with ingredients with lower risk like glycerol or sorbitol in this age group.
EVALuna2:18933